Inovação em produtos tradicionais transmontanos: a perceção do consumidor acerca de novos produtos derivados da alheira - Estevinho, Leticia M. (2018)
This work is part of a project developed under PRODER, measure 4.1-Cooperation for innovation, dedicated to the development of new products derived from alheira, namely, snacks with alheira filling. It results from a partnership between a research unit and an industrial company. Tasting tests were developed in which 129 individuals, aged between 18 and 90 years, with a mean age of 56.4 years (SD = 16,244) participated. Most participants found the new product agreeable or very agreeable referring their intention to purchase the product when the product will be available for sale. The results showed that there is great acceptability of the new product by consumers. That gives the company the possibility to diversify its products and increase its economic results.